2003
DOI: 10.1124/jpet.103.055327
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Agonist-Mediated Heterologous Desensitization in Isolated Ileum Requires Activation of Both Muscarinic M2 and M3 Receptors

Abstract: We investigated the subtypes of the muscarinic receptor mediating short-term heterologous desensitization in the isolated ileum. Treatment of the ileum from C57BL/6 mice with acetylcholine (30 M) for 20 min caused a subsequent decrease in contractile sensitivity to both prostaglandin F 2␣ (PGF 2␣ ) and the muscarinic agonist, oxotremorine-M. This subsensitivity was characterized by 7-and 3-fold increases in the EC 50 values of the agonists, respectively, with no significant effect on the maximal response. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The pK B values estimated for 4-DAMP from the data just described as well as those in Fig. 3 are similar to the binding affinity of 4-DAMP estimated at human M 3 muscarinic receptors expressed in CHO cells (pK D ϭ 8.81), but not with that estimated at human M 2 muscarinic receptors (pK D ϭ 7.87) (Griffin et al, 2004). In these latter assays, binding was measured in a modified KRB buffer similar to that used in the present study.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The pK B values estimated for 4-DAMP from the data just described as well as those in Fig. 3 are similar to the binding affinity of 4-DAMP estimated at human M 3 muscarinic receptors expressed in CHO cells (pK D ϭ 8.81), but not with that estimated at human M 2 muscarinic receptors (pK D ϭ 7.87) (Griffin et al, 2004). In these latter assays, binding was measured in a modified KRB buffer similar to that used in the present study.…”
Section: Resultssupporting
confidence: 70%
“…To test this idea, we measured the competitive antagonism of oxotremorine-M-induced contractions by 4-DAMP in ileum and trachea. 4-DAMP exhibits 10-fold higher binding affinity for human M 3 muscarinic receptors (pK D ϭ 8.81) expressed in CHO cells compared with human M 2 receptors (pK D ϭ 7.87) (Griffin et al, 2004). At a concentration of 10 nM, 4-DAMP caused similar shifts (10.2-and 15.9-fold) in the oxotremorine-M concentration-response curve in ileum and trachea, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…The contractions elicited by carbachol or oxotremorine-M in the ileum (Matsui et al 2002;Unno et al 2005;Griffin et al 2009) and gastric fundus and antrum (Stengel et al 2000(Stengel et al , 2002Kitazawa et al 2007) undergo a small loss of function in the M 2 KO mouse (two-fold increase in agonist EC 50 , with no decrease in E max ), a large loss of function in the M 3 KO mouse (50-70% reduction in E max ), and a complete loss in the M 2 /M 3 double KO mouse. The contractions measured in antrum, fundus, and ileum from the M 2 KO mouse are competitively inhibited by the antagonists, N,N-dimethyl-4-piperidinyl diphenylacetate (4-DAMP) (M 3 -over M 2 -selective) and AF-DX 116 (M 2 -over M 3 -selective) with pK B values (approximately 9.0 and 6.0, respectively) that agree with M 3 binding affinity [8.8 and 6.1, respectively (Esqueda et al 1996;Griffin et al 2004)]. Conversely, the pK B values of 4-DAMP and AF-DX 116 in the same tissues from the M 3 KO mouse (approximately 8.3 and 7.3, respectively) agree with M 2 -binding affinity [7.9 and 7.3, respectively (Esqueda et al 1996;Griffin et al 2004)].…”
Section: Antagonism Of Agonist-induced Contraction Of Gastrointestinamentioning
confidence: 79%
“…We found that after five successive carbachol CRCs, the affinity of the M 3 -selective antagonist para-fluoro hexahydro siladifenadol was shifted to a lower value, consistent with M 2 receptors participating in the contraction (data not shown). Others have shown that the M 3 receptor subtype is subject to agonist-induced desensitization (Tobin et al, 1992;Willets et al, 2001Willets et al, , 2002Griffin et al, 2004). Therefore, M 3 receptor desensitization may occur during the repeated agonist CRCs, which could explain these differences.…”
Section: Discussionmentioning
confidence: 98%